The Use of Container Types on The Physical Characteristics and Quality of Tomato (Lycopersicon Ensculentum Miller) - Saputra, Arya Iswardana; Pudja, Ida Ayu Rina Pratiwi; Sumiyati , Sumiyati (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
This study aims to determine the effect of the type of container (bamboo basket, plastic basket, and cardboard) on the physical characteristics and quality of tomatoes during the distribution process using ground transportation simulation. This study used a 2 factorial randomized block design (RBD) with 3 repetitions. The results of this study indicate that the maximal physical damage occurred in the bamboo basket container within 5 hours of treatment because the bamboo basket has rough sides and high porosity of 4.078% (physical damage in the form of increased scratches and bruises and decreased hardness). Minimal damage occurred in the cardboard container with a 1-hour treatment because it has a smooth coating of the container and not too high porosity, namely 3.960%. The best container to use in the tomato distribution process using a ground transportation simulation is a cardboard container (having low porosity the cardboard and a smooth container layer) so can be maintained the condition of the tomatoes.